Mid-term clinical results of chronic cavitary long bone osteomyelitis treatment using S53P4 bioactive glass: a multi-center study - T. A. G. Van Vugt (Copernicus Publications, 2021)
Introduction: Chronic osteomyelitis is a challenging condition in the orthopedic practice and traditionally treated using local and systemic antibiotics in a two-stage surgical procedure. With the introduction of the antimicrobial biomaterial S53P4 bioactive glass (Bonalive®), chronic osteomyelitis can be treated in a one-stage procedure. This study evaluated the mid-term clinical results of patients treated with S53P4 bioactive glass for long bone chronic osteomyelitis. Methods: In this prospective multi-center study, patients from two different university medical centers in the Netherlands were included. One-stage treatment consisted of debridement surgery, implantation of S53P4 bioactive glass, and treatment with culture-based systemic antibiotics. If required, wound closure by a plastic surgeon was performed. The primary outcome was the eradication of infection, and a secondary statistical analysis was performed on probable risk factors for treatment failure. Results: In total, 78 patients with chronic cavitary long bone osteomyelitis were included. Follow-up was at least 12 months (mean 46; standard deviation, SD, 20), and 69 patients were treated in a one-stage procedure. Overall infection eradication was 85 %, and 1-year infection-free survival was 89 %. Primary closure versus local/muscular flap coverage is the only risk factor for treatment failure. Conclusion: With 85 % eradication of infection, S53P4 bioactive glass is an effective biomaterial in the treatment of chronic osteomyelitis in a one-stage procedure. A major risk factor for treatment failure is the necessity for local/free muscle flap coverage. These results confirm earlier published data, and together with the fundamentally different antimicrobial pathways without antibiotic resistance, S53P4 bioactive glass is a recommendable biomaterial for chronic osteomyelitis treatment and might be beneficial over other biomaterials.